Public Awareness in ensuring Animal Originated Food Safety : A Review on “One Health” Approach in Veterinary Medicine - Estoepangestie, A. T. Soelih (KnE Life Sciences, 2017)
Human and animals live in the same ecosystem bound one to another interdependently and build an harmony in an ecosystem. Since the time of Hippocrates, the One Health concept has existed, which is now we can find in AVMA’s web page, the words “on Airs, Waters, and Places”. One of the One Health’s founders is an epidemilogist, Dr. Calvin W. Schwabe, captured the word “One Medicine” in his book, Veterinary Medicine and Human Health. Now we live in this century can feel the existence of various health problems involving human health and animal health affected one to another. Antimicrobial resistance issues is nowadays one of the challenge facing the medicine. Veterinary Services has a plenty history of applying veterinary public health principles to protect human health through animals and animal products saftey. The Veterinary role in the AMR problems is not a question. The use of drugs, includes antimicrobial, in veterinary practices can not be hindered, that is all to ensure safety not just for animals but also for humanbeing. Microbes contamination in the preparation of animal originated food, from farm to fork, is the main problem in connection to the animal originated food safety. Public services in this field is the entry point of microbes contamination which causing the decrease of food quality. To change the people’s behaviour in processing of animal originated food chain is not easy. Continuing public awareness in preparing safety food is one of athe best way to ensure the intelectuality of a nation Keywords: Global health problem; Animal originated food ; Food safety in Indonesia; Human-animal health interactions; From farm to fork; Public awareness